2007
DOI: 10.1101/gad.1544507
|View full text |Cite
|
Sign up to set email alerts
|

The functional interplay between EGFR overexpression, hTERT activation, and p53 mutation in esophageal epithelial cells with activation of stromal fibroblasts induces tumor development, invasion, and differentiation

Abstract: Esophageal cancer is a prototypic squamous cell cancer that carries a poor prognosis, primarily due to presentation at advanced stages. We used human esophageal epithelial cells as a platform to recapitulate esophageal squamous cell cancer, thereby providing insights into the molecular pathogenesis of squamous cell cancers in general. This was achieved through the retroviral-mediated transduction into normal, primary human esophageal epithelial cells of epidermal growth factor receptor (EGFR), the catalytic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
161
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(167 citation statements)
references
References 49 publications
6
161
0
Order By: Relevance
“…It was previously demonstrated that culturing EPC2-hTERT-EGFR-p53 R175H cells, which overexpress EGFR and contain a p53 missense mutation, in a three-dimensional organotypic culture induced the invasion of these cells into the extracellular matrix (20). Michaylira et al (21) reported that the induction of periostin, which was preferentially expressed in invading cells, was dependent upon EGFR signaling and p53 mutation.…”
Section: Periostin In Esophageal Cancermentioning
confidence: 99%
“…It was previously demonstrated that culturing EPC2-hTERT-EGFR-p53 R175H cells, which overexpress EGFR and contain a p53 missense mutation, in a three-dimensional organotypic culture induced the invasion of these cells into the extracellular matrix (20). Michaylira et al (21) reported that the induction of periostin, which was preferentially expressed in invading cells, was dependent upon EGFR signaling and p53 mutation.…”
Section: Periostin In Esophageal Cancermentioning
confidence: 99%
“…3D cell cultures are well documented to regain intrinsic properties and to better mimic the in vivo situation than cells cultured as monolayers on plastic (Dolznig et al, 2011;Fischbach et al, 2009;Okawa et al, 2007;Pickl and Ries, 2009). Studies have shown that the gene expression profiles (Takagi et al, 2007) as well as the responses to treatment (Desoize and Jardillier, 2000) in the multicellular spheroid 3D models resemble more closely the in vivo situation.…”
Section: Introductionmentioning
confidence: 99%
“…This approach results in a mature stratified epithelium that is morphologically similar to the native oesophagus and which has been incorporated into a number of experimental procedures [13][14][15][16] . However there is little published characterisation of this model itself and the approach does not include a basement membrane (BM).…”
Section: Introductionmentioning
confidence: 99%